1996
DOI: 10.1590/s0074-02761996000100001
|View full text |Cite
|
Sign up to set email alerts
|

Classification of immature stage habitats of Culicidae (Diptera) collected in Córdoba, Argentina

Abstract: In order to classify mosquito immature stage habitats, samples were taken in 42 localities of Córdoba Province, Argentina, representing the phytogeographic regions of Chaco, Espinal and Pampa. Immature stage habitats were described and classified according to the following criteria: natural or artificial; size; location related to light and neighboring houses; vegetation; water; permanence, movement, turbidity and pH. Four groups of species were associated based on the habitat similarity by means of cluster an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 13 publications
4
65
1
1
Order By: Relevance
“…quinquefasciatus was collected from artificial containers, deep pools, and ditches, the last containing abundant decaying organic matter, in accordance with other authors' reports (Lourenço-de-Oliveira et al 1986, Campos et al 1993, Almirón & Brewer 1996, Oria et al 1999. Lourenço-de-Oliveira et al (1986) collected a specimen in a natural rock excavation.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…quinquefasciatus was collected from artificial containers, deep pools, and ditches, the last containing abundant decaying organic matter, in accordance with other authors' reports (Lourenço-de-Oliveira et al 1986, Campos et al 1993, Almirón & Brewer 1996, Oria et al 1999. Lourenço-de-Oliveira et al (1986) collected a specimen in a natural rock excavation.…”
Section: Discussionsupporting
confidence: 76%
“…Cux. bidens has also been found in tires (Stein et al 2007) and in metal containers (Almirón & Brewer 1996). Almirón and Brewer (1996) found Oc.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Almirón & Brewer (1996) collected C. saltanensis that had colonized natural habitats and artificial reservoirs in Córdoba Province, Argentina. Lourenço-de-Oliveira & Heyden (1986) observed that the species is predominantly ornithophilous, although eclectic when choosing its host.…”
Section: Lourençomentioning
confidence: 99%